Fundamentals of Entrepreneurship (ENT 300) Business Model Canvas / Nurul Afrina Mohamed Halim - Mohamed Halim, Nurul Afrina (2020)
Our business name is called as ‘Healthy Bowl’. The name of our business means that we serve a healthy food that served in bowl for our beloved customers. The tagline of the business is ‘Eat Healthy, Live Better’. This tagline is to encourage people to eat healthy food because it can help us to maintain a healthy weight and reduces our risk from many diseases. The healthy food products that we would like to offer is overnight oat and smoothie bowls. Our food product is to help people who have difficult to eat a healthy food because it is not so tasty especially for beginner who just starting to eat healthy food.